Role of Nursing Care in Recovery of Burn Injuries among the Victims of Domestic Violence - Zulfiqar Ali Buzdar, Annum Bashir, Mansoora Mirza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burns due to domestic violence are responsible for physical abuse as well as emotional scars in long term consequences. Domestic violence can range from physical harm to sexual, psychological, and economic abuse, and it often escalates over time. Burns are one of the finest manifestation of domestic violence including severe pain, disfigurement and long term health complications. The recovery phase is also subject to mental, social and physical stress. Survivors are subject to experience severe anxiety, depression and post-traumatic stress disorder. Nursing care is what that can be answer to all above described mental and physical stress in the recovery phase or period of hospitalization. Aim: To explore whether the nursing care do play a role in recovery of burn injuries inflicted due to domestic violence. Methodology: The study included 250 victims of burns due to domestic violence who presented in AED of the Jinnah Hospital and filtered in the medicolegal clinic of the AIMC Lahore during the January to August period of the year 2018. An observational researched method was applied to rural and urban areas of the jurisdiction of said research setting. Results: The study results show that professional nursing care and specialized health services plays a pivotal role with a grossly significant p value of 0.000 helping the burn victims of domestic violence to recover from their injuries as compared to general nursing services. The terminal outcome as also found significant with 0.025 p value. Conclusion: The specialized health services and professional nursing care can significantly alter the outcome of the burn injuries. The likely outcome and complications can be avoided if a better and targeted services in reference to burn care could be rendered to the injuries of burns due to domestic violence. Hence the study emphasizes on the practicality of the role of nursing care as a vital aspect in terms of recovering from burning injuries. Keywords: Burns, Domestic, Violence, Nursing Care, Injuries, Recovery